Mengkaji Teori Humanistik Dalam Novel Hayy Ibn Yaqdzhan Karya Ibnu Thufail - Hidayah, Fathi (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2017)
Humanistic theories evolved from the discontent of anxiety in the behavioristic and psychoanalytic theories that regard humans as passive objects of learning. Appearing in the Renaissance and confirmed as a new learning theory in the 20th century, the humanistic theory proved to be a forerunner long before. Ibn Thufail, a Muslim philosopher during the Spanish Muwahid dynasty, spawned a humanistic-themed work in the 12th century. The stages of the theory of need even to the peak of self-actualization as defined by Abraham Maslow the father of modern humanistic psychology are summarized in a story from a a little boy named Hayy ibn Yaqdzan. Keywords: humanistic psychology, Abraham Maslow, Hayy ibn Yadzan